The efficiency of some bioagent fungi in reduction of wheat seed decay and seedling damping-off disease with heavy metals interaction - Qusai Madhi; MOHAMMED HAMZA ABASS; ABDULNABI ABDUL AMEER MATROOD (Society for Indonesian Biodiversity, 2021)
Abstract. Madhi QH, Abass MH, Matrood AAA. 2021. The efficiency of some bioagent fungi in reduction of wheat seed decay and seedling damping-off disease with heavy metals interaction. Biodiversitas 22: 3984-3993. Biological control is an ecofriendly efficient measurement for disease control and heavy metals reduction in soils. The use of bioagent fungi such as Trichoderma koningii and Chaetomum globosum reduced the negative effect of pathogenic fungi that cause seed decay and the seedlings damping off wheat alone or by interaction with the concentrations of lead or cadmium, which increases the germination percentage of wheat seeds and reducing seedling damping off. It also reduced the severity index of wheat with pathogenic fungi and reduced the negative effect of interaction between heavy metals and pathogenic fungi on the severity index of the wheat. Results showed that T. koningii and C. globosum reduced the effect of the interaction of R. solani with 200 mg/kg lead to 57.7 and 55.4%, respectively and R. solani and cadmium 3 mg/kg with 60 and 61.6%, respectively. T. koningii and C. globosum also reduced the effect of the interaction F.solani with lead 200 mg/kg to 45.4 and 48.5%, respectively and F. solani and cadmium 3 mg/kg to 46.8 and 52.5% respectively. The bioagent fungi also increased the fresh and dry weight of shoot and root system, T. koningii significantly increased the fresh and dry weight of shoot in the presence of R. solani. The results also indicated that there was a high significant difference in the use of C. globosum in increasing the fresh and dry weight of shoot and root system. T. koningii and C. globosum significantly reduced the effect of interaction between the pathogenic fungi and low concentrations of lead and cadmium leading to an increase in the fresh and dry weight of shoot and root system. They also increased the plant height in the presence of pathogenic fungi as well as reducing the negative effect of the interaction between heavy metals and pathogenic fungi in the height of wheat plants. No significant interaction was observed between the low concentrations of lead and cadmium and pathogenic fungi in the presence of bioagent fungi. The results exhibited that bioagent fungi can reduce the negative effect of interaction of pathogenic fungi with lead and cadmium on the total phenols content of wheat leaves, and no significant difference was recorded in the treatment of low concentrations with the pathogenic fungi. Results showed that bioagent fungi can reduce the negative effect of the interaction of pathogenic fungi with lead and cadmium on the total phenols content of wheat plant leaves. No significant differences were recorded in the treatment of low concentrations with the pathogenic fungi in the presence of bioagent fungi. The two bioagent fungi increased the concentration of chlorophyll a and b, total chlorophyll and carotenoids reduced anthocyanin in leaves, and increased chlorophyll stability index compared to the control treatment.